The Follow-Up of Chinese Patients in cblC Type Methylmalonic Acidemia Identified Through Expanded Newborn Screening - Ling, Shiying; Wu, Shengnan; Shuai, Ruixue; Yu, Yue; Qiu, Wenjuan; Wei, Haiyan; Yang, Chiju; Xu, Peng; Zou, Hui; Feng, Jizhen; Niu, Tingting; Hu, Haili; et al. (Frontiers in Genetics, 2022)
Abstract Objective: The cblC type of combined methylmalonic acidemia and homocystinuria, an inherited disorder with variable phenotypes, is included in newborn screening(NBS) programs at multiple newborn screening centers of China. The present study aimed to investigate the long-term clinical benefits of screened individual. Methods: A national, retrospective multi-center study of infants with confirmed cblC defect identified by NBS between 2004 to 2020 was conducted. We collected a large cohort of 538 patients and investigated their clinical data in detail, including disease onset, biochemical metabolites and gene variation , and explored different factors on the prognosis. Results: Long-term outcomes of all patients were evaluated, representing 44.6% for poor outcomes. By comparison of patients already occurring clinical signs before treatment with asymptomatic ones, intellectual impairment, movement disorders , ocular complications , hydrocephalus and death were comparable (P<0.01). Presence of disease onset (Odd ratio [OR] 12.39, 95%CI 5.15-29.81; P =0.000), variants of c.609G>A(Odd ratio [OR] 2.55, 95%CI 1.49-4.35; P =0.001) and c.567dupT (Odd ratio [OR] 2.28, 95%CI 1.03-5.05; P =0.042) were independently associated with poor outcomes, especially for neurodevelopmental deterioration. Conclusion: NBS, avoiding major disease-related events and allowing an earlier treatment initiation, appeared to have a protective effect on the prognosis of infants with cblC defect.